A review and analysis of the taxonomy and nomenclature of the Kalanchoe species (Crassulaceae subfam. Cotyledonoideae) of Royal Botanic Gardens, Kew, botanist John Gilbert Baker (1834–1920), all of which were published in the late-19 century - Smith, Gideon F. (Phytotaxa, 2025)
A review and analysis is presented of the Kalanchoe species (Crassulaceae subfam. Cotyledonoideae) described by John Gilbert Baker (1834–1920), the first botanist to have been appointed, in January 1866, as First Assistant in the Herbarium of the Royal Botanic Gardens, Kew, after Joseph Dalton Hooker (1817–1911) had been appointed as Director of the institution on 1 November 1865. Baker, an accomplished botanist, published 18 names and one designation in Kalanchoe—one of these names was published in Cotyledon—for taxa today included in Kalanchoe. This excludes the kalanchoes for which Baker at first published names in Kitchingia. Baker did not himself transfer any of the kitchingias to Kalanchoe. The nomenclature and taxonomy of the names published in Kalanchoe, and the one published in Cotyledon, by Baker, and that of the designation that he published in Kalanchoe, are reviewed and discussed in a historical context. The types of the names of Baker’s kalanchoes are reviewed.